Administration by roaming and its impact on the institutional performance in the Palestinian governmental institutions - Milhem, Marwan; Ateeq, Ali; Badwan, Sameh Mahmoud; Ali, Shafeeq Ahmed; Alzoraiki, Mohammed; Al Astal, Ahmad Yahia; Ibrahim, Siddig (Frontiers in Human Dynamics, 2026)
This research investigates the impact of management by walking around (MBWA) on the performance of the Palestinian Ministry of Agriculture. MBWA prioritizes face-to-face relationships between supervisors and staff members to improve communication, motivation, and feedback. Data was gathered from 185 workers out of a total of 328 in the directorates of Jenin, Tulkarm, Nablus, Qalqilya, and Tubas in the northern West Bank. This was done using a structured questionnaire and a descriptive-analytical approach. Participants were selected using a stratified random sampling procedure. The survey assessed the characteristics of MBWA, including fact-finding, feedback, and motivation, and examined their influence on institutional performance. The reliability and validity of the data were verified by the use of Cronbach’s Alpha and composite reliability tests. A statistical study, which included correlation and regression analysis, was conducted to evaluate connections and ascertain the influence of MBWA practices on institutional performance. The statistical research demonstrated that MBWA practices have a considerable influence on institutional performance. Feedback (β = 0.444, p = 0.006) and motivation (β = 0.304, p = 0.03) shown a positive correlation with improved performance. Nevertheless, the process of gathering information revealed that there was no noteworthy direct impact (β = 0.189, p = 0.131). MBWA contributed 32.4% to the variation in institutional performance, underscoring its efficacy in enhancing results via improved feedback and motivation. Nonetheless, the process of information collection had little effect. Future studies should investigate the long-term impacts and wider application of MBWA across diverse governmental settings.